HZ.AİŞE’NİN EVLİLİK YAŞI ETRAFINDAKİ TARTIŞMALAR - Suzan Yıldırım (İstem, 2004)
In this article, the issue of how old Aisha, the third wife of the Prophet Muhammad, was when she got married has been dealt with. First, Arab custom regarding the age of marriage has been put forward. Secondly, the account in hadith collections and siyar (The biography of the Prophet) works have been scrutinized. Both classical Islamic scholars and moder n scholars differ in their approaches to the issue of the age of Aisha when she was engaged and married. Lastly, we drew attention to the fact that our prejudices and worldviews have an effect on our perception of the historical events and facts